2012
DOI: 10.1007/s00300-012-1236-x
|View full text |Cite
|
Sign up to set email alerts
|

Growth responses of Sphagnum hollows to a growing season lengthening manipulation in Alaskan Arctic tundra

Abstract: The global increase in surface air temperature has produced an overall lengthening of the growing season by 3-5 days/decade in the Northern Hemisphere during the last 30 years. The direct impact of a longer growing season has not been well documented for Sphagnum moss communities in the Arctic. We hypothesized that an increase in the growing season length may be detrimental to Sphagnum growth as a result of photoinhibition caused by the plants emerging from snow near the seasonal peak of solar irradiance. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…We thus used the T gs , the arithmetic average temperature of the months above 0 • C, as the growth temperature for the whole plant of Sphagnum. In fact, Sphagnum growth during the months of freezing temperature does occur if snow cover was thick and persistent enough to insulate Sphagnum from winter frost (Dorrepaal et al, 2004;Genet et al, 2013), as snow cover shading is not is not a major limiting factor for Sphagnum growth (Clymo and Hayward, 1982;Küttim et al, 2020). That being said, biomass production of Sphagnum during freezing months is much reduced.…”
Section: Uncertainty In Constraining the Time Span Of Precipitation Imentioning
confidence: 99%
See 1 more Smart Citation
“…We thus used the T gs , the arithmetic average temperature of the months above 0 • C, as the growth temperature for the whole plant of Sphagnum. In fact, Sphagnum growth during the months of freezing temperature does occur if snow cover was thick and persistent enough to insulate Sphagnum from winter frost (Dorrepaal et al, 2004;Genet et al, 2013), as snow cover shading is not is not a major limiting factor for Sphagnum growth (Clymo and Hayward, 1982;Küttim et al, 2020). That being said, biomass production of Sphagnum during freezing months is much reduced.…”
Section: Uncertainty In Constraining the Time Span Of Precipitation Imentioning
confidence: 99%
“…However, the cumulative temperature-such that is defined as growing degree days above zero in bioclimatic studies (Charman et al, 2013)-might be a more accurate measure of the total warmth Sphagnum have experienced. Studies found that Sphagnum productivity at a given site is enhanced during the warmest season (Krebs et al, 2016;Küttim et al, 2020), although a few studies suggested that Sphagnum growth could be limited by summer desiccation stress and photoinhibition (Lindholm, 1990;Dorrepaal et al, 2004;Genet et al, 2013). Certainly, there is a tendency that T gs would underestimate the mass-weighted growth temperature for the whole plant of Sphagnum.…”
Section: Uncertainty In Constraining the Time Span Of Precipitation Imentioning
confidence: 99%
“…In the southern-most parts of this region, more precipitation will arrive in liquid form and be available earlier in the season for hydropower generation, rather than stored in the snowpack until spring melt. In the Far North, ET is a relatively small portion of the hydrologic budget and precipitation dominates (Kane et al, 1990), though ET will increase as the growing season continues to lengthen as it has in recent decades (Genet et al, 2013;Olchev and Novenko, 2011;Zeng et al, 2011). Other aspects of the supply side, which include groundwater storage and glacier storage, will be addressed in the next section on regional complexity.…”
Section: Climate Change Impacts On Hydropower Supply and Demandmentioning
confidence: 99%
“…In the southern-most parts of this region, more precipitation will arrive in liquid form and be available earlier in the season for hydropower generation, rather than stored in the snowpack until spring melt. In the Far North, ET is a relatively small portion of the hydrologic budget and precipitation dominates (Kane et al, 1990), though ET will increase as the growing season continues to lengthen as it has in recent decades (Genet et al, 2013;Olchev and Novenko, 2011;Zeng et al, 2011). Other aspects of the supply side, which include groundwater storage and glacier storage, will be addressed in the next section on regional complexity.…”
Section: Climate Change Impacts On Hydropower Supply and Demandmentioning
confidence: 99%